Executive Committee Minutes 2010-05-06 - Academic Senate:::::::::
Agenda approved. Minutes of 4/1/10 approved. Chair Report. President Report. Provost Report. Program Track in ELSE for Communication Development, Revision to Specialist Program in ELSE, Revision to English Single Subject Credential, and New Minor in Queer Studies approved for Senate consent calendar. Online forum concerning the financial management of SSU proposal amended and approved for Senate agenda. FSAC Report. Representation on Administrative Appointment Committees policy approved for Senate agenda. Changes to Structure and Functions in the by-laws approved for the Senate agenda. Revision to WEPT policy approved for Senate agenda. SAC Report. FSAC Report continued. Senate agenda approved.